Dysfunctions in B2B relations with a supplier in the supply chain - Marcinkowski, Jakub Mateusz; Kutzner, Iwona Małgorzata; Bożydaj-Jankowska, Iwona (Dysfunkcje w relacjach B2B z dostawcą w łańcuchu dostaw, 2019)
The main goal of the article is to attempt to identify the way to analyse dysfunctions in B2B relations with a supplier in the supply chain. The subject of the analysis is the relationship between a supplier producing a food supplement and a customer (a consignee) in the pharmaceutical industry supply chain. The customer is a pharmaceutical corporation in which the supply chain department is responsible for contacts with suppliers. The article aims to answer the question whether and if so, what kind of dysfunctions occur in B2B relations in the supply chain and how can they be characterized? The dysfunctions indicated by the authors: transport and storage, administrative and legal as well as communication are an innovative approach to the presented issue. The ability to eliminate or at least minimize individual forms of the dysfunctions shapes the impact on mutual relations, which are characterized by the uneven dependence, the more so when they manifest themselves in the long-term perspective
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 7, s. 256-270
Keywords: dysfunctions; B2B; supply chain; pharmaceutical supply chain; relations; dysfunkcje; łańcuch dostaw; branża farmaceutyczna; relacje